2023
DOI: 10.1088/1361-6463/acd5de
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of discharge mode transition of air plasma under pulsed and sinusoidal excitations

Abstract: The transition from O3 to NOx discharge mode is common for air plasma with an increase of discharge power density, which greatly changes the chemistry of the plasma as well as its application effect. Although this discharge mode transition has been intensively studied in recent years, differences between plasmas subject to pulsed or sinusoidal excitations have rarely been reported on. In this study, a surface dielectric barrier discharge is excited using either a microsecond pulsed voltage or a sinusoidal volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The intensity of all bands decreased at 4.8 kV. This is easy to understand since higher intensity of discharge results in a higher emission intensity [28]. No emission lines of O, OH, and hydrogen atoms were observed due to low concentration of H 2 O in the air.…”
Section: Optical Emissionmentioning
confidence: 77%
See 2 more Smart Citations
“…The intensity of all bands decreased at 4.8 kV. This is easy to understand since higher intensity of discharge results in a higher emission intensity [28]. No emission lines of O, OH, and hydrogen atoms were observed due to low concentration of H 2 O in the air.…”
Section: Optical Emissionmentioning
confidence: 77%
“…The 180 • configuration demonstrated a similar trend of discharge intensity with an area of low intensity clearly seen in the top view. The white color in both bending configurations suggested that the discharge intensity was much higher in that area [28]. By analyzing the image brightness and spatial distribution status, the distribution of discharge images is shown in figure 4 for the two voltages of 4.8 and 5.4 kV for the three configurations studied.…”
Section: Discharge Imagesmentioning
confidence: 97%
See 1 more Smart Citation